THE ROLE OF KODIM 0618/BS IN BANDUNG ANALYSIS IN THE EFFORT OF REDUCING NATURAL DISASTERS IN BANDUNG CITY - Zaqy, Fithra Luthfi Bahri; Thamrin, Suyono; Lasmono, Lasmono (Indonesia Defense University, 2018)
Kodim 0618/BS of Bandung City is a unit of Military District Command under the Kodam III/Siliwangi Command which oversees as many as 14 Koramil that are spread in the area of Bandung City. With 14 Koramil spread across the city of Bandung, Kodim 0618/BS has 347 personnel and stands by itself because it is not under the Korem and tasked with regional empowerment, defense and preparing all aspects of regional defense including having their own programs and handling in reducing the risk of natural disasters. This research is conducted to find out the role of Kodim 0618/BS in the Effort of Reducing Natural Disasters in Bandung, which has a high potential for natural disasters because it is located between the Lembang Fault and geographically is in the form of a basin which means it has a high risk of flood. This study employs qualitative method. The data was obtained through observation, interviews and library studies. Descriptive analytical techniques were employed in conjunction with data collection when researchers were in the research site – Bandung. The research finds that 1) The role of Kodim 0618/BS in Efforts of Reducing Natural Disasters is essential with Dandim being the deputy chairman in the Satlak of Disaster Mitigation and Reduction and 2) Bandung City uses the Fire Department and Natural Disaster Management as an organization responsible for Natural Disaster Management 3) There is a lack of Disaster Mitigation Experts, hence special training for personnel is neededKeywords: Disaster Management, Natural Disaster, Main Duty of TNI